2020
DOI: 10.3389/fonc.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-22 Contributes to Epithelial-Mesenchymal Transition in Osteosarcoma by Targeting Twist1

Abstract: The epithelial-mesenchymal transition (EMT) is a vital step in osteosarcoma (OS) progression toward metastasis, but the specific molecular events governing this process are incompletely characterized, with miRNAs having increasingly been found to regulate the EMT. In this study, We assessed levels of miR-22 and its target, Twist1, via real-time PCR (qRT-PCR). We further used functional proliferation assays, measures of cell morphology, and western blotting to assess the functional relevance of miR-22 in OS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…EMT is a crucial process that participated in the metastasis of OS. 27,29 And in the present study, we found that EMT markers E-cadherin and N-cadherin were associated with the expression of CASC15/miR-338-3p/RAB14 axis, indicating that CASC15/miR-338-3p/RAB14 axis can regulate the invasion and metastasis of OS via EMT.…”
Section: Dovepresssupporting
confidence: 62%
“…EMT is a crucial process that participated in the metastasis of OS. 27,29 And in the present study, we found that EMT markers E-cadherin and N-cadherin were associated with the expression of CASC15/miR-338-3p/RAB14 axis, indicating that CASC15/miR-338-3p/RAB14 axis can regulate the invasion and metastasis of OS via EMT.…”
Section: Dovepresssupporting
confidence: 62%
“…Various long non-coding RNAs and miRNAs have been shown to regulate the EMT and, thus, affect the metastatic behavior of tumor cells [ 74 ]. Especially, these RNAs modulate the expression of transcription factors, such as zinc finger E-box binding homeobox 1 (ZEB1) [ 77 , 78 , 79 ], Twist1 [ 80 ], or signal transducer and activator of transcription 3 (STAT3) [ 81 ] and signaling pathways, including the Wnt/β-catenin and NOTCH pathways [ 82 , 83 ].…”
Section: Mechanisms Of Metastasis Formationmentioning
confidence: 99%
“…Plasma levels of miR-22 were also found to be an independent diagnostic and prognostic biomarker in osteosarcoma (Diao et al, 2020). Moreover, at the cellular level, miR-22 overexpression impaired proliferation and EMT in osteosarcoma by targeting Twist1 (Zhu et al, 2020). These studies suggest that EMT and distant metastasis are tightly regulated in osteosarcoma.…”
Section: Discussionmentioning
confidence: 79%